Volumenska in vrednostna zgradba ter priraščanje visokokakovostnih bukovih sestojev v Sloveniji - Kadunc, Aleš (Zbornik gozdarstva in lesarstva, 2005)
The aim of the paper was to establish the structure of growing stocks, current volume increment, (commercial) value of growing stocks and current (commercial) value increment by different social collectives in highquality beech stands. In order to do so, beech stands from 18 site units were analysed, with analyses of five plots measuring 30 x 30 m carried out on each site unit. For all trees above the measurement threshold, the stem analyses were performed. The stem quality was estimated by quarters. On this basis, the volume, current decade volume increment, value and current decade value increment of stands were established. More than 90% of volume and even aslightly higher share of value go to the trees from the stand canopy. The collective of 100 the thickest trees per hectare covers about half of the stands volume or stands value. The percentage of sliced veneer quality is extremely low (3%), while the percentage of peeled veneer quality is five times higher. The highest values are achieved by stands from mountainous beech sites.
Keywords: bukovi gozdovi; lesna zaloga; prirastek